Answer:
x = 25
Step-by-step explanation:
Given:
- ∠A = ∠B (Vertically opposite angles)
- ∠A = (7x - 8)°
- ∠B = (6x + 17)°
Since ∠A is equivalent to ∠B...
![\implies (7x - 8)= (6x + 17)](https://tex.z-dn.net/?f=%5Cimplies%20%287x%20-%208%29%3D%20%286x%20%2B%2017%29)
Open the parenthesis:
![\implies 7x - 8= 6x + 17](https://tex.z-dn.net/?f=%5Cimplies%207x%20-%208%3D%206x%20%2B%2017)
Add 8 both sides:
![\implies 7x - 8 + 8= 6x + 17 + 8](https://tex.z-dn.net/?f=%5Cimplies%207x%20-%208%20%2B%208%3D%206x%20%2B%2017%20%2B%208)
Simplify both sides:
![\implies 7x = 6x + 25](https://tex.z-dn.net/?f=%5Cimplies%207x%20%3D%206x%20%2B%2025)
Subtract 6x both sides:
![\implies 7x - 6x = 6x - 6x + 25](https://tex.z-dn.net/?f=%5Cimplies%207x%20-%206x%20%3D%206x%20-%206x%20%2B%2025)
Simplify both sides:
![\implies x = 25](https://tex.z-dn.net/?f=%5Cimplies%20x%20%3D%2025)
Answer:
1)60
2)7
Step-by-step explanation:
1)The square root of 3600 is 60. It is the positive solution of the equation x2 = 3600. The number 3600 is a perfect square.
2)The cube root of 343 is the number which when multiplied by itself three times gives the product as 343. Since 343 can be expressed as 7 × 7 × 7. Therefore, the cube root of 343 = ∛(7 × 7 × 7) = 7.
Answer:
2
Step-by-step explanation: